Application of postmortem radiographs: advantages & disadvantages a case report / Wong Yi-Li ... [et al.] - Wong, Yi-Li; Krishnan, Vomanasri; Ibrahim, Norliza; Mohamad Noo, Mohamad Helmee (Faculty of Medicine, 2021)
Postmortem radiograph skeletal surveys serve as imaging adjuncts to autopsy and forensic documentation in hospitals with no available forensic computed tomography and magnetic resonance imaging services. Despite this, modern literature pertaining practical applications of postmortem radiographs have gradually been superseded by interests in advanced imaging modalities. The main advantages are characterizing or excluding violent traumatic bone fractures or abnormalities, locating foreign bodies, identifying medical devices as well as acting as secondary adjuncts to anthropologic assessment. Limitations that test diagnostic value of postmortem radiographs include lack of direct visualization of soft tissue as well as postmortem artefacts that obscure natural causes of death and can be misinterpreted as antemortem pathology. The roles and limitations of postmortem radiographs are illustrated in a case of a decomposed but complete and identified adult male decedent with reference to autopsy findings and literature review.